Dietary phytase effects on copper requirements of broilers - Soster, Patricia; Vieira, Sergio Luiz; Feijo, Julmar Costa; Altevogt, Walter Edmundo; Tormes, Giovane B. (Frontiers in Veterinary Science, 2023)
Availability of Cu from plant feedstuffs for broilers in the presence of phytase is scarce. The present research has been conducted with the objective of evaluating Cu requirements of broilers when fed corn-soy diets with or without phytase. A total of 640 one-day-old male Cobb x Cobb 500, allocated into 80 battery cages with 8 chicks in each, were fed a low Cu content diet (formulated with 8.58 ± 0.21 mg/kg Cu) without phytase from placement to 7 d. Starting on day 8, battery cages were distributed into a 2 X 5 factorial arrangement (phytase added diets X 5 graded increases of supplemental Cu) until 28 days. Feeding treatments (feeds added or not with phytase and 5 graded increases of Cu) were randomly distributed with 8 cages of 8 chicks. The basal non supplemented feeds were formulated with corn and soybean meal (SBM) without any other significant Cu contributors. Supplemental Cu was from laboratory grade Cu sulfate pentahydrate (CuSO5H20) which was increasingly added to the feeds. Phytase was added in excess to the producer recommendation (2,500 FYT) and had average analyzed values of 2,768 ± 135.2 FYT/kg whereas analyzed Cu were: 8.05 ± 0.25, 11.25 ± 0.15, 14.20 ± 0.40, 16.55 ± 0.05, 19.45 ± 0.45 mg/kg. Statistics were conducted using linear and quadratic polynomial regression models. No interactions occurred between dietary Cu and phytase (P>0.05) for any response and no effects were found for the individual factors (phytase or dietary Cu) for Ht, Hb, varus, valgus, rotated tibia, tibia breaking strength, as well as for Cu contents in breast, gastrocnemius tendon and kidney (P>0.05). However, phytase added diets led to higher BWG, lower FCR, increased ileal digestible Cu (P<0.05). The gradual increase in dietary Cu produced linear increases in Cu content in livers, as well as in excreta and retention (P < 0.05). Supplementing phytase at levels expected to maximize phytate degradation demonstrated to improve BWG and FCR; however, no effects were observed when dietary Cu was increased to a maximum of 19.45 mg/kg. An increase of 8.8% in ileal digestible Cu was observed when birds were fed phytase.